2014
DOI: 10.1007/s11356-014-3194-z
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use by giant panda in relation to man-made forest in Wanglang Nature Reserve of China

Abstract: To evaluate the effectiveness of human restoration in species conservation, in this study, we undertook a field survey of giant panda (Ailuropoda melanoleuca) habitat and man-made forest habitat in Wanglang Nature Reserve of China. Our results revealed that giant panda did not use the man-made forest in this area so far, and that there were significant differences between the giant panda habitat and the man-made forest habitat. Compared with giant panda habitat, the man-made forest habitat was characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Previously, we have found that the giant panda did not use the artificial forest habitat in the Wanglang Nature Reserve 15 . In this study, we still did not find the entity of giant panda and any trace of giant panda activity in the artificial forests and artificial forest plots, but we found a significant difference between the artificial forest and giant panda habitat in terms of plant species composition, community structure, and community collocation, which together may explain the giant panda’s lack of use of artificial forest in this area.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, we have found that the giant panda did not use the artificial forest habitat in the Wanglang Nature Reserve 15 . In this study, we still did not find the entity of giant panda and any trace of giant panda activity in the artificial forests and artificial forest plots, but we found a significant difference between the artificial forest and giant panda habitat in terms of plant species composition, community structure, and community collocation, which together may explain the giant panda’s lack of use of artificial forest in this area.…”
Section: Discussionmentioning
confidence: 96%
“…For example, after approximately 50 years of natural recovery, logged habitats were able to function again as suitable giant panda habitat in the Wolong Nature Reserve 11 . Artificial restoration can rapidly increase the vegetation coverage 12 , but some studies have suggested that giant panda seldom and even hardly use the artificial forest 13–15 . Under this situation, only by identifying the defects of artificial restoration and rectifying them can we hope to better understand the reason for its failures, and thus improve its protective effect for the giant panda.…”
Section: Introductionmentioning
confidence: 99%
“…To study the resting site characteristics of giant pandas, we visited the giant panda resting sites that we located in field surveys conducted in April, May, July, August, October, November, and December of 2012 14 ; March and April of 2013 30 ; and December 2015 in the Wanglang Nature Reserve. A resting site plot was established when a giant panda resting site was encountered in the field and was centralized on the resting site with a size of 5 m × 5 m. Seven variables were measured in each resting site plot (Table 5).…”
Section: Methodsmentioning
confidence: 99%
“…Our main objective was to investigate the characteristics of resting sites in order to determine the factors affecting the resting time of giant pandas. We were particularly interested in the slope of the habitat and the nature of the surrounding vegetation (trees, shrubs, and bamboo) because these are important factors affecting the habitat use of the giant panda 12,14,30,36,37 . We hope this timely report will provide basic data for understanding the resting habits of giant pandas and serve as an important reference for giant panda protection.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Artificial afforestation with the purpose of producing wood is not suggested. Traditional afforestation can increase the forest cover rapidly, but it usually involved planting single species, even-aged, and fast-growth individual trees with a high density, with little regard given to the function restoration, it can provide almost no habitat for giant panda and cannot fulfill the habitat requirements of them (Kang et al 2014). Giant pandas require habitat that comprises an entire functioning ecosystem for their survival (Li and Shen 2012), rather than a simple assembly of planted trees.…”
mentioning
confidence: 99%